Faktor Pendukung dan Penghambat Pelaksanaan Program Penguatan Pendidikan Karakter Religius Terhadap Siswa - Melinda Pridayani; Ahmad Rivauzi (An-Nuha, 2022)
This study aims to determine the supporting and inhibiting factors for the implementation of a strengthening program of religious character education for students in SMP Negeri 13 Padang which is accredited A in the city of Padang, West Sumatra. The research uses qualitative methods through a case study approach. Research data sources are taken from fourteen informants consisting of school principals, Islamic Religious Education teachers, and students of class IX.8 Research data were taken through in-depth interviews with all informants. The results showed that the implementation of the program for strengthening the religious character education of students at SMP Negeri 13 Padang had four supporting factors including the existence of a student character strengthening book, the desire of students, supporting religious activities, and adequate facilities and infrastructure. While the five inhibiting factors include: environment, peers, and cellphones. self-awareness of students themselves and lack of teacher supervision.